2013
DOI: 10.1093/mnras/stt985
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy triplets in Sloan Digital Sky Survey Data Release 7 - II. A connection with compact groups?

Abstract: We analyse a sample of 71 triplets of luminous galaxies derived from the work of O'Mill et al. (2012). We compare the properties of triplets and their members with those of control samples of compact groups, the ten brightest members of rich clusters, and galaxies in pairs.The triplets are restricted to have members with spectroscopic redshifts in the range 0.01 z 0.14 and absolute r-band luminosities brighter than M r = −20.5. For these member galaxies, we analyse the stellar mass content, the star formation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 47 publications
6
24
0
Order By: Relevance
“…This is in agreement with the results given in Duplancic et al (2013) who show that SDSS-triplets present an important fraction of bulge-type, red galaxies, with low star formation activity indicators, similarly to galaxy members of compact groups.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the results given in Duplancic et al (2013) who show that SDSS-triplets present an important fraction of bulge-type, red galaxies, with low star formation activity indicators, similarly to galaxy members of compact groups.…”
Section: Discussionsupporting
confidence: 93%
“…Only three triplets contain the majority of star-forming galaxies (classified as 111, 112 and 113), mostly in the low mass bin. This result is in agreement with Duplancic et al (2013), who found that blue triplets are located in the less massive tail of the total stellar mass distribution and present an efficient star formation activity when compared to compact groups, in the same stellar mass bin. As the fractions of AGNs and passive galaxies increases, the number of triplets with a dominance of passive and retired galaxies (mainly 233 and 333) increases.…”
Section: The Combination Of Whan Classes According To Triplet Propertiessupporting
confidence: 93%
“…Further analysis carried out by Duplancic et al (2013), based on photometric colours and star formation activity, indicates that galaxy triplets present similar properties to compact groups and that these systems, comprising luminous galaxies, are actually an extension of compact galaxy groups with a smaller number of members. A dynamical analysis, employing the AA-diagram (Agekyan & Anosova 1968) and mock catalogues, also indicates that their configurations provide better conditions for interaction and mergers between galaxy members (Duplancic et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…In O-sample, there are about one tenth of the triplets with spectroscopic redshifts for all their members. Duplancic et al (2013Duplancic et al ( , 2015 analyzed the configuration and dynamics of this sub-sample, and compared them with galaxy pairs and clusters. They found that the triplet galaxy members are more similar to the galaxies in compact groups and rich clusters than in galaxy pairs and concluded that the galaxy triplets may not be formed hierarchically.…”
Section: Introductionmentioning
confidence: 99%